Development of Automated Monitoring System for Hydroponics Vertical Farming - GW, Michael; Fei Siang, Tay; Yi Lung, Then (IOP Publishing Ltd., 2021)
Proposed is an automated monitoring system for hydroponics vertical farming. This project aims to design and develop an automated system to monitor and maintain the level of nutrition solution for the vertical farming process. The monitoring condition includes Electrical Conductivity (EC), pH value, the liquid level as well as the water temperature of the nutrient solution stored in the rectangular PVC. Instead of using soil as the growing medium, the project used hydroponics method to grow the leafy vegetables, Bok Choy. The data monitored will be sent and processed by Arduino Mega microcontroller and upload to Ubidots Cloud using the ESP8266 NodeMCU. The system also provides control function to maintain the nutrient level and amount of solution flows into each layer of vegetables. It is expected that the implemented system would reduce the water and electrical consumption and allows the growth of the plant to be supervised from time to time without having a person to look after.